An evaluation of a global vitamin and mineral nutrition surveillance system. - Jennings Aburto, Nancy; Rogers, Lisa; De-Regil, Luz Maria; Kuruchittham, Vipat; Rob, Grace; Arif, Raheel; Peña-Rosas, Juan Pablo (Archivos Latinoamericanos de Nutrición, 2013)
Evaluation at all levels is a fundamental function at World Health Organization (WHO). Evaluation of public health surveillance systems is essential to ensure that problems of public health importance are monitored efficiently and effectively. The WHO's Vitamin and Mineral Nutrition Information System (VMNIS) was evaluated from the perspective of public health surveillance and informatics. Steps included: engaging the stakeholders of the evaluation; describing the surveillance system; focusing the evaluation design; gathering credible evidence regarding system performance; justifying and stating conclusions and recommendations, and sharing lessons learned from the evaluation. Following this assessment, WHO has begun major efforts to upgrade and expand the VMNIS and now the database is more flexible and efficient. The database evaluation summarized in this paper provides a good example of how public health evaluation frameworks can lead to improved surveillance and enhanced information systems, thus making progress toward the ultimate goal of improving public health.